ANALISIS PERHITUNGAN BIAYA RATA-RATA PELAYANAN PASIEN RAWAT INAP DALAM PEMENUHAN STANDAR PELAYANAN MINIMAL (STUDI KASUS PADA RSUD SEKAYU KABUPATEN MUSI BANYUASIN) - jumania septariani (Universitas Prof.Hazairin,SH Bengkulu, 2020)
This study discussed the calculation of the average cost of inpatient services in meeting the Minimum Service Standards at Sekayu District General Hospital in achieving hospital service assessment indicators. This study examined financial data within a period of 3 (three) years, namely 2017-2019. In this study, the author used quantitative descriptive analysis techniques. Quantitative descriptive technique used was by calculating the average cost of inpatient services in meeting the Minimum Service Standards at the Sekayu District General Hospital of Musi Banyuasin and analyzing the level of utilization of health service facilities, quality of service, and level of service efficiency by calculating assessment indicators hospital services. The calculating results of achieved indicators that was Bed Occupancy Rate (BOR) of 90.8%, Average Length of Stay (Av LOS) was for 3 days, Bed Turn Over (BTO) was by 85 times, Turn Over Inverval (TOI) was for 1 day, Gross Death Rate (GDR) was of 1 person, Net Death Rate (NDR) was of 1 person.